1980
DOI: 10.1530/jrf.0.0600449
|View full text |Cite
|
Sign up to set email alerts
|

The number of oocytes and the rate of atresia in unilaterally ovariectomized mice up to 8 months after surgery

Abstract: Summary. Random

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…It is concluded that growth in length of the uterus occurs during the implantation reaction and this may assist in the accommodation of blastocysts along the length of the uterus. [10] A single horn of the mice uterus is provided for the development of as many as 12 young pups, after 3 weeks[11] and the single remaining ovary in unilaterally ovariectomized animals (assuming the number of corpora lutea to be an index of ovulation) produces as many ova as both ovaries in normal females.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that growth in length of the uterus occurs during the implantation reaction and this may assist in the accommodation of blastocysts along the length of the uterus. [10] A single horn of the mice uterus is provided for the development of as many as 12 young pups, after 3 weeks[11] and the single remaining ovary in unilaterally ovariectomized animals (assuming the number of corpora lutea to be an index of ovulation) produces as many ova as both ovaries in normal females.…”
Section: Discussionmentioning
confidence: 99%
“…At this age ‘growing oocytes’ (in stage II-VI follicles) have a single nucleolus that can be used as a counting marker; ‘pool oocytes’ (in stage I follicles) still may have multiple nucleoli and were counted when the nucleus was judged to be cut near the middle (Baker et al, 1980; Jones and Krohn, 1961). …”
Section: Methodsmentioning
confidence: 99%
“…The sections were stained with hematoxylin and eosin and analyzed under a light microscope (Olympus, Tokyo, Japan; type CH2). The nucleoli point counting method of Mandel and Zuckerman ('50,'51) modified by Baker et al (1980) was used to calculate the number of oocytes in the analyzed females. In this method each oocyte (all oocytes except class I and II) with a clearly visible nucleolus is scored.…”
Section: Histological Analysis Of the Ovaries And Kidneysmentioning
confidence: 99%